The geography of electoral volatility in Hungary: a core-periphery perspective - Bertus, Zoltán; Kovács, Zoltán (Hungarian Geographical Bulletin, 2022)
Electoral volatility is understood in the literature as a sign of political instability, weakening social cohesion and the declining influences of existing political parties which threatens the healthy functioning of representative democracy. In this paper, using the Pedersen Index we measure electoral volatility in Hungary at the settlement level between the last three parliamentary elections (2010, 2014 and 2018), with special attention to the geographical aspects of the phenomenon. According to our preliminary assumptions those social groups switch their votes frequently who are marginalised, therefore, the level of volatility may reflect peripheriality. Our results show that high volatility can be detected in the two opposite sides of the settlement hierarchy in Hungary: in bigger cities and smaller villages, but for very different reasons. This study gives evidence that electoral volatility can also be considered as a possible indicator in the delimitation and classification of peripheral areas and settlements. The paper aimed to contribute to the understanding of cleavage formation at the regional level by adding a spatial perspective while connecting the socioeconomic profile of the voting population and electoral volatility.